Light-Processed 3D Bioprinting of Symblepharon Rings Fortified with l-Ascorbic Acid for Ocular Tissue Engineering - ULAĞ, SONGÜL; GÜNDÜZ, OĞUZHAN (My University, 2024)
This study aims to develop gelatin methacryloyl (GelMA)-based symblepharonrings fortiﬁed with l-ascorbic acid (lAA), aiming for controlled release ofvitamins for the treatment of the ocular surface, corneal healing, andacceleration of epithelial growth, while concurrently preventing potentialinﬂammation. The human tears contain abundant IAA, which serves aprotective role for ocular tissues. The utilization of 3D printing digital lightprocessing technology not only navigating the manufacturing process ofsymblepharon rings, addressing challenges related to commercial productionand expedited delivery to patients but also imparts enhanced ﬂexibilitycompared to commercial products. This innovative approach also facilitatesthe production of rings that exhibit superior softness and are amenable tomechanical movements for ocular tissue engineering. The morphological,chemical, rheological, biological, thermal, and drug-release characteristics of3D-printed lAA-loaded symblepharon rings are investigated. In themorphological characterization, it is observed that the rings exhibit a porousstructure. In biocompatibility tests, Gelas and Gelas-low rings achieve over75% viability. Following the cell test, scanning electron microscope imagesreveal ﬁbroblasts adhering to Gelas and Gelas-low rings, spreading acrosstheir surfaces. Drug release studies conducted in phosphate-buﬀered saline atpH 7.4 reveal the complete release of lAA from Gelas-low within a 5-dincubation period.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Temel Bilimler (SCI); Mühendislik; Malzeme Bilimi; MÜHENDİSLİK, KİMYASAL; POLİMER BİLİMİ; KİMYA, ORGANİK; MALZEME BİLİMİ, ÇOKDİSİPLİNLİ; Engineering, Computing & Technology (ENG); Natural Sciences (SCI); ENGINEERING; MATERIALS SCIENCE; CHEMISTRY; ENGINEERING, CHEMICAL; POLYMER SCIENCE; CHEMISTRY, ORGANIC; MATERIALS SCIENCE, MULTIDISCIPLINARY; Genel Kimya Mühendisliği; Fizik Bilimleri; Polimerler ve Plastikler; Organik Kimya; Malzeme Kimyası; General Chemical Engineering; Physical Sciences; Polymers and Plastics; Organic Chemistry; Materials Chemistry; DLP printing; GelMA; l-ascorbic acid; symblepharon rings